Necrotising fasciitis of odontogenic origin - Chunduri, Nagendra Srinivas (BMJ Publishing Group, 2013)
Necrotising fasciitis (NF) is a rare infection of the fascial planes, which is less common in head and neck, because of the rarity and higher vascularity in the region. We report a case of necrotising fasciitis in a 43-year-old man, arising from a dental infection treated successfully by early diagnosis, prompt surgical management, antibiotic therapy and adjunctive hyperbaric oxygen (HBO) therapy. The diagnosis of descending NF must always be considered in a patient who presents with a history of oropharyngeal infection with evidence of neck swelling, chest pain, and dyspnea or respiratory distress. Aggressive surgical debridement of all involved tissue along with intravenous antibiotic therapy should be initiated before aerobic and anaerobic cultures are obtained. HBO may also be of some benefit in the treatment of this potentially fatal infection.